Determinants of prenatal care use and HIV testing during pregnancy: a population-based, cross-sectional study of 7080 women of reproductive age in Mozambique - Sanni Yaya; Olanrewaju Oladimeji; Kelechi Elizabeth Oladimeji; Ghose Bishwajit (BMC, 2019)
Abstract Background In low-income countries with poor coverage of healthcare services such as Mozambique, antenatal care serves as a vital tool for providing life-saving and cost-effective services for pregnant mothers. Nonetheless, many countries in Africa, including Mozambique, are struggling to attain an optimum level of antenatal care (at least 4 visits) utilisation among pregnant women. In the present study, we aimed to assess the sociodemographic and economic factors associated with antenatal care use in Mozambique. Methods Cross-sectional data from the latest round of Mozambique Demographic and Health Survey (2011) on women aged 15-49 years (n = 7080) were analysed. The outcome measures were early and adequate antenatal visit and HIV tests during the last pregnancy. Data were analysed using descriptive and multivariate regression methods. The predictor variables included various demographic (e.g. age, parity), empowerment (e.g. type of employment, household wealth status) and sociocultural factors (e.g. ethnicity, religion). Results Of the 7080 women whose data was analyzed, 15.3 and 60.1% had early and adequate ANC visits respectively while 75.4% received HIV test during ANC visits. The odds of early ANC visits were higher [OR = 1.300, 95%CI = 1.062,1.592] among women in the rural areas compared with those in the urban areas. However, participants in rural areas had lower odds [OR = 0.788, 0.687,0.902] of receiving HIV tests during ANC visits. Women in the urban areas with secondary [OR = 1.296, 95%CI = 1.007,1.666] and higher [OR = 1.663, 95%CI = 1.052,2.628] education had higher odds of having early ANC visit. Those in the higher wealth quintiles also had significantly increased odds of using all three types of ANC indicators, particularly for rural women in the highest wealth quintile [OR = 4.776, 95%CI = 1.250,18.24]. Being within the higher wealth quintiles was found to significantly increase the odds of using all three types of ANC indicators, particularly women from rural areas with highest wealth quintile [OR = 4.776, 95%CI = 1.250,18.24]. Conclusion About two-fifth of the women in Mozambique are not using adequate antenatal care and about and a quarter do not take HIV tests during pregnancy. The sources of low and unequal use of these vital health services might be rooted in women's socioeconomic status and cultural issues that require special policy and research attention.